Microcontroller-based Forklift Path Following Robot Prototype - Tresnawati, Shandy; Ekawati, Nia; Siddiq, Maulana Fadjar (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The development of science in the field of robotics has made many heavy jobs that cannot be done by humans replaced by robots, especially in the factory industry. In modern factories, most of them have a warehouse or similar facility that contains heavy equipment for use in a factory, for example, forklift heavy equipment. Based on an interview with one of the forklift operators, the problem of using forklifts is usually when there are items that must be moved that cannot be lifted by humans which must be done immediately according to the route where the item is stored. To answer the existing problems, a robot prototype was made which is useful to help facilitate the work of factory workers. This robot prototype was built using the User Centered Design (UCD) method. This robot prototype uses the main components of Arduino UNO, L293D Motor Driver, and PWM Servo Motor Driver. Based on the overall testing that has been done, it can be said that the robot prototype can follow the route according to the program and can lift and remove objects in front of it with a score of 80%. So that workers can be helped to facilitate their work.